1991
DOI: 10.1007/bf00401514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic systemic insulin delivery on insulin action in dogs

Abstract: The metabolic consequences of the prolonged systemic insulin delivery associated with human pancreas transplantation have not been precisely defined. To determine if systemic insulin delivery in the absence of immunosuppressive agents results in alterations in hepatic or extrahepatic insulin action, three groups of dogs were studied 2 months after either a sham operation or after their pancreatic venous drainage was severed and anastomosed to the inferior vena cava or portal vein (sham, peripheral and portal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Isoglycaemic hyperinsulinaemic clamp data in normal and diabetic pigs after 4 weeks of peripheral and hepatic insulin delivery can remove between 50 and 75 % of insulin in the fasting state [55]. A lack of agreement exists among previous animal investigations, performed in rodents or dogs, concerning whether or not insulin delivery by the peripheral route results, as in our study, in raised [3,7,9,13,[17][18][19][20][21] or unchanged [2,6,11,[14][15][16] peripheral insulin levels. Studies in man comparing intraperitoneal and subcutaneous insulin delivery have similarly yielded conflicting results relating to the extent of systemic insulinisation [23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Isoglycaemic hyperinsulinaemic clamp data in normal and diabetic pigs after 4 weeks of peripheral and hepatic insulin delivery can remove between 50 and 75 % of insulin in the fasting state [55]. A lack of agreement exists among previous animal investigations, performed in rodents or dogs, concerning whether or not insulin delivery by the peripheral route results, as in our study, in raised [3,7,9,13,[17][18][19][20][21] or unchanged [2,6,11,[14][15][16] peripheral insulin levels. Studies in man comparing intraperitoneal and subcutaneous insulin delivery have similarly yielded conflicting results relating to the extent of systemic insulinisation [23][24][25][26][27][28]56].…”
Section: Discussioncontrasting
confidence: 63%
“…A number of investigations have supported the concept that only portal insulin delivery can sustain normal insulin responsiveness [13,18,20]. Others, however, have yielded contradictory findings [2,4,7,11,14,17,19].…”
Section: : 1125-1134]mentioning
confidence: 99%
“…In addition, the aforementioned study in phosphorylation-defective CEACAM1-mutant mice (33) showed that a change in insulin clearance results in hyperinsulinemia without a change in insulin secretion and the subsequent development of hepatic insulin resistance. Also, in dogs (19,34), when pancreatic insulin delivery bypasses the liver completely and is diverted directly to the systemic circulation, hyperinsulinemia results, with the subsequent development of peripheral insulin resistance. Our results indicate development of hepatic insulin resistance primary or secondary to the decrease in liver insulin clearance when obesity is induced by a moderate-fat diet.…”
Section: Discussionmentioning
confidence: 98%
“…However, when phlorizin is used instead of insulin to reduce plasma glucose, insulin-mediated skeletal muscle glucose uptake is normalized (32), and glucose transport and transporter translocation are improved (28). Thus, three hypotheses can be proposed to explain the inability of insulin therapy to restore glucose uptake, transport, and transporter translocation in human diabetes, as well as in the rat model of diabetes: ( a ) although insulin treatment reduces glucose level, the increase in plasma insulin induced by the chronic insulin therapy might exert per se a negative effect on insulin-stimulated muscle glucose uptake (34)(35)(36); ( b ) subcutaneous insulin therapy in rats cannot produce a completely normal glucose profile: variable high and low glucose values adversely influence glucose uptake by muscle; and/or ( c ) the insulin therapy was not adequate in terms of route of administration (37), because insulin was not administered in the portal system, as occurs physiologically, but subcutaneously into the peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%